Management information systems project study on Philippine Coconut Authority - Atienza, Elvira; Cue, Michael; Santos, Ma. Rosal; Talens, Ma. Carmelita; Tan, Jack (College of Engineering, 1987)
Before the choice of the Philippine Coconut Authority as our project site, the group considered several other agencies, namely, the Philippine National Oil Company (PNOC), the National Steel Corporation (NSC), the Philippine Fish Marketing Authority (PFMA), the Philippine National Railways (PNR) and the Ministry of Natural Resources (MNR). Because we were advised to pick on a government agency, the choice was made among PCA, MNR and PFMA. Government agencies or service agencies are favored for this project since previous project studies were conducted in private companies which are production-oriented. PCA deals with the affairs of the coconut industry and being one of the top dollar-earners of the country, it has captured the interest of the group. We wanted to know why the coconut industry earned the title and what role PCA plays in boosting the coconut industry. We were quite intrigued, too, of the functions of the PCA and how it monitors coconut producers from all over the Philippines. These factors, aside from the PCA?s obvious proximity to the University of the Philippines campus, were enough reasons for the group to finally choose PCA for its project site.